Peran ATR/BPN Kanwil Jatim dalam Penyelesaian Konflik Agraria: Studi Kasus Sengketa Tanah Mbaon Desa Senggreng Kecamatan Sumberpucung Malang - M. Ithomas Alfiansyah (Al-DYAS, 2026)
Although agrarian conflicts have been widely studied, the resolution of land disputes involving multiple actors and overlapping authority among institutions remains a complex issue, particularly in the case of Tanah Mbaon in Senggreng Village, Malang Regency. This study aims to analyze the role of ATR/BPN Kanwil Jawa Timur in resolving the conflict and to identify the approaches used. This study employed a qualitative approach with a literature study design and analysis of relevant documents. The results showed that ATR/BPN acted as a mediator and facilitator through legal-formal approaches, administrative audits, and participatory mediation involving various parties. These approaches proved capable of encouraging a conflict resolution process that was more systematic, inclusive, and just, although limitations of authority and multi-actor complexity remained the main challenges. These findings affirm that the resolution of agrarian conflicts requires the integration of legal and social approaches in a collaborative manner. This study contributes to strengthening the study of agrarian conflict resolution and underscores the importance of cross-institutional coordination and the development of participatory-based conflict resolution models.